Bioactive Ti + Mg composites fabricated by powder metallurgy: The relation between the microstructure and mechanical properties. (February 2019) - Balog, Martin; Ibrahim, Ahmed Mohamed Hassan; Krizik, Peter; Bajana, Oto; Klimova, Alena; Catic, Amir; Schauperl, Zdravko
Abstract: Metallic implant materials are biomaterials that have experienced major development over the last fifty years, yet some demands posed to them have not been addressed. For the osseointegration process and the outcome of endosseous implantation, it is crucial to reduce the stress shielding effect and achieve sufficient biocompatibility. Powder metallurgy (PM) was utilized in this study to fabricate a new type of titanium (Ti) + magnesium (Mg) bioactive composite to enable stress-shielding reduction and obtain better biocompatibility compared with that of the traditional Ti and Ti alloys used for dental implants. Such composites are produced by well-known cost-effective and widely used PM methods, which eliminate the need for complex and costly Ti casting used in traditional implant production. The relation between the microstructure and mechanical properties of as-extruded Ti + (0–24) vol% Mg composites was investigated with respect to the Mg content. The microstructure of the composites consisted of a biodegradable Mg component in the form of filaments, elongated along the direction of extrusion, which were embedded within a permanent, bioinert Ti matrix. As the Mg content was increased, the discrete filaments became interconnected with each other and formed a continuous Mg network. Young's modulus (E) of the composites was reduced to 81 GPa, while other tensile mechanical properties were maintained at the values required for a dental implant material. The corrosion behavior of the Ti + Mg composites was studied during immersion in a Hank's balanced salt solution (HBSS) for up to 21 days. The elution of Mg pores formed at former Mg sites led to a further decrease of E to 74 GPa. The studied compositions showed that a new Ti + Mg metallic composite should be promising for load-bearing applications in endosseous dental implants in the future.